Basilar Artery Dolichosis Increases the Risk of Long–Term Recurrence in Patients With Pontine Infarction: A Prospective Cohort Study - Cao, Shugang; Zhu, Xiaoxia; Wu, Qian; Ni, Xiaoxing; He, Jun; Cui, Ping; Ge, Tingting; Wang, Jian; Xu, Wen'an; Xia, Mingwu (Frontiers in Neurology, 2021)
Background and Purpose: Patients with basilar artery (BA) dolichosis are at high risk of acute pontine infarction (API), but the association between BA dolichosis and long–term stroke recurrence has received little attention. We aimed to identify the effect of BA dolichosis on the risk of long–term brainstem infarction recurrence in patients with API. Methods: In this prospective cohort study, we enrolled 113 patients with API admitted to our department. BA dolichosis was diagnosed by a BA curve length > 29.5 mm or bending length (BL) > 10 mm on magnetic resonance angiography. The primary outcome was the occurrence of diffusion–weighted imaging (DWI)–confirmed brainstem infarction. The Cox proportional hazard model was used to detect possible predictors of brainstem infarction recurrence. Results: Among 113 patients with API, 39 (34.5%) patients had BA dolichosis, and DWI–confirmed brainstem infarction recurred in 15 (13.3%) patients with a mean follow–up time of 31.2 months; the estimated 5–year incidence of brainstem infarction recurrence was 23.1% in patients with BA dolichosis, which was significantly higher than the incidence of 8.1% in patients without BA dolichosis. Cox proportional hazard analysis showed that age ≥ 65 years (hazard ratio (HR) = 3.341, 95% confidence interval (CI): 1.079–10.348, P = 0.036) and BA dolichosis (HR = 3.048, 95% CI: 1.069–8.693, P = 0.037) were significantly associated with a higher risk of brainstem infarction recurrence. In a subgroup analysis stratified by age, the patients aged ≥ 65 years with BA dolichosis had a higher risk of brainstem infarction recurrence (HR = 7.319, 95% CI: 1.525–35.123, P = 0.013). Conclusions: This study indicates that BA dolichosis may increase the risk of long–term brainstem infarction recurrence in patients with API, especially in elderly patients, and therefore warrants more attention in clinical practice.